Pengaruh Kebijakan Pengelolaan Sdm Dan Pengembangan Karir Terhadap Kinerja Pegawai Dengan Motivasi Kerja Sebagai Variabel Intervening Pada Kantor Dinas Tanaman Pangan Hortikultura Dan Perkebunan Kabupaten Lima Puluh Kota - Ilhamsyah Putra; Robby Dharma; Omia Crefioza (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to examine the extent to which human resource management and career development influence employee performance, with motivation serving as an intervening variable, at the Lima Puluh Kota Food Crops, Horticulture, and Plantation Agency. Data collection was conducted through surveys and the distribution of questionnaires to a sample of 84 respondents. The analysis method employed was Structural Equation Modeling (SEM) using SmartPLS. The results indicate a positive and significant influence of human resource management on motivation, and of career development on motivation, at the agency. Furthermore, positive and significant influences were found regarding the impact of human resource management and career development on employee performance, as well as the impact of motivation on employee performance. Finally, the study reveals positive and significant influences of human resource management and career development on employee performance mediated by motivation.